Relation between Food Security and Breastfeeding and Feeding Practices with the Event of Stunting to Children in Poor Family in Langkat Regency - Syahrani Khaira Irmi; Evawany Y. Aritonang; Etti Sudaryati (Randwick International of Social Science Journal, 2022)
Stunting is one of the health and nutritional problems that are often experienced by toddlers as a result of not fulfilling food intake for a long time, causing toddlers' height to be inappropriate for their age. In 2021 the prevalence of stunting in Indonesia is 24.4 percent. Langkat Regency is one of the regencies in North Sumatra, where stunting is a health and nutrition problem with a prevalence of 31.5 percent. This study aims to analysist the relationship between food security and breastfeeding and feeding practices with the incidence of stunting under five in poor families in Langkat Regency. This research is a quantitative study with a cross sectional design with a sample of 238 children under five. The results showed that there was a relationship between food security (p < 0.001) and the practice of breastfeeding and food (p < 0.001) with the incidence of stunting under five. Suggestions for this research to health workers are expected to carry out health education about healthy and nutritious food intake and mothers are expected to be able to fulfill healthy and nutritious food intake for toddlers so that toddlers' growth and development are optimal.